2012
DOI: 10.1111/j.1464-410x.2012.11288.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes in men with lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH) treated with intraprostatic OnabotulinumtoxinA: 3‐month results of a prospective single‐armed cohort study

Abstract: E 8 3 7What ' s known on the subject? and What does the study add? Several short-term studies have shown that intraprostatic injection of botulinum toxin (BTX) improves lower urinary tract symptoms and fl ow parameters in patients with BPH, but information on patient-reported outcomes is lacking.The present study provides useful data on patient-perceived level of improvement and effectiveness of intraprostatic injection of BTX, as well as on patient ' s satisfaction with this therapy. Short-term results are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 41 publications
2
20
0
2
Order By: Relevance
“…61 In an independent study, 67% of patients were satisfied with treatment with 200 units of BoNTA after 3 months of treatment; unsurprisingly, a similar number (68%) judged the treatment to be effective. 63 Results of these pilot studies seem promising, although other studies have not consistently shown the same results. 64,65 Furthermore, results of a randomized, double blind, placebo controlled phase II trial, published in 2013, failed to indicate any significant improvements in either urinary symptom scores or prostate measures in patients with LUTS and BPH who were treated with either BoNTA or placebo.…”
Section: Bph and Male Lutsmentioning
confidence: 90%
“…61 In an independent study, 67% of patients were satisfied with treatment with 200 units of BoNTA after 3 months of treatment; unsurprisingly, a similar number (68%) judged the treatment to be effective. 63 Results of these pilot studies seem promising, although other studies have not consistently shown the same results. 64,65 Furthermore, results of a randomized, double blind, placebo controlled phase II trial, published in 2013, failed to indicate any significant improvements in either urinary symptom scores or prostate measures in patients with LUTS and BPH who were treated with either BoNTA or placebo.…”
Section: Bph and Male Lutsmentioning
confidence: 90%
“…BoNT-A injection in smaller prostate glands caused a much lesser reduction in prostate volume, but a 15% reduction was still observed [32,36]. Independent of the extent of prostate volume reduction, improvements in LUTS and flow have been consistently reported [29][30][31][32][44][45][46][47][48][49][50][51][52][53], while a decrease in total serum PSA was observed in some studies [e.g. 30,45,51], but not in others [52].…”
Section: Botulinum Toxinmentioning
confidence: 90%
“…Published studies on Botox reported that 200 U of Botox reconstituted with normal saline to a volume of 20% of the total prostate volume is required for the injections into the transition zone and peripheral zone of the prostate gland and to avoid any penetration into the bladder [53]. Common adverse events such as hematuria, difficult urination, perineal pain and acute prostatis, is likely related to inadvertent penetration of the injection needles into the prostatic urethra and bladder neck [53][54][55].…”
Section: Benign Prostatic Hyperplasiamentioning
confidence: 96%
“…Animal studies showed that intraprostatic BoNT-A injections can induce selective denervation and subsequent apoptosis and atrophy of the prostate gland [52]. Prostatic injections of BoNT-A can be performed using transperineal, transrectal or transurethral routes [53][54][55]. Published studies on Botox reported that 200 U of Botox reconstituted with normal saline to a volume of 20% of the total prostate volume is required for the injections into the transition zone and peripheral zone of the prostate gland and to avoid any penetration into the bladder [53].…”
Section: Benign Prostatic Hyperplasiamentioning
confidence: 99%